Using standard CETSCALE and other adapted versions of the scale for measuring consumers' ethnocentric tendencies: An analysis of dimensionality - José Felipe Jiménez-Guerrero; Juan Carlos Gázquez-Abad; Emilia del Carmen Linares-Agüera (BRQ Business Research Quarterly, 2014)
The consumer ethnocentrism tendencies scale (CETSCALE) was developed by Shimp and Sharma in 1987 to measure consumer ethnocentrism. It is one of the most commonly used scales in the marketing literature. As well as the original 17-item version, there are many empirical applications using other adapted versions of CETSCALE. These versions differ in terms of the number (and composition) of items, incorporating additional items and even accounting for the nationality of the foreign products under study. Some of these papers question the unidimensionality of such a scale. We intend to analyse the dimensionality of the CETSCALE. In order to do this, an extensive review of previous studies that have considered CETSCALE—whatever the version—is developed. In addition, we analyse the dimensionality of an adapted version of the CETSCALE including the product category (vegetables) under study. Our results support the multidimensionality of the CETSCALE."
Keywords: 650; Ethnocentrism; CETSCALE; Consumer